METHODOLOGY OF DIGITAL ASSESSMENT OF STUDENTS' PROFESSIONAL COMPETENCIES IN VOCATIONAL EDUCATION INSTITUTIONS (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The contemporary landscape of vocational education is characterized by a widening gap between the competencies certified through traditional assessment instruments and the actual professional readiness demanded by employers in rapidly evolving labor markets. This article addresses the systemic inefficiency of conventional, paper-based examination methods in capturing the multidimensional nature of professional competencies and proposes a comprehensive digital assessment methodology as a strategic mechanism for transforming competency evaluation in vocational education institutions (VEIs). By integrating formative digital tools, adaptive testing platforms, and employer-validated competency matrices into a unified assessment ecosystem, the proposed methodology aims to enhance assessment validity, increase transparency of evaluation processes, and align certification outcomes with real-sector workforce requirements. The first part of this study critically analyzes the theoretical foundations of competency-based assessment, drawing upon the Evidence-Centered Design framework and the Constructive Alignment theory. It establishes the conceptual framework for shifting from a summative, knowledge-recall model to a continuous, performance-based digital assessment paradigm that captures both cognitive and applied dimensions of professional competence.